Eksplorasi Makna Hidup Anak Gen Z di Era Digital - Najmi, Akmalun; Ismail, Ismail; Romli B, Moh (Abdurrauf Journal of Education and Islamic Studies, 2025)
The digital era has brought about fundamental changes in how Generation Z interprets life, amid the flood of information and widespread use of social media. The methodology in this study uses qualitative research through literature review to understand the elements, challenges, and opportunities in the formation of their meaning of life. The results of this study indicate that digital media, social media, and digital spaces play a significant role in the process of identity formation and the search for meaning in life for Generation Z. However, on the other hand, they also pose challenges in the form of digital distractions, identity crises, and concerns about the future. Family, social community, education, and information technology skills can play a role in helping Gen Z children find authentic, spiritual meaning in life and have a positive impact in the digital age. This study emphasizes that cooperation between families, schools, and communities is essential to improve digital literacy and self-awareness so that Generation Z can use technology wisely in finding direction and meaning in their lives. Abstrak: Era digital telah menghasilkan banyak perubahan mendasar untuk cara generasi Z dalam menginterpretasikan kehidupan, di tengah derasnya informasi dan penggunaan media sosial secara luas. Metodologi dalam penelitian ini menggunakan penelitian kualitatif melalui kajian pustaka yang bertujuan untuk memahami elemen, tantangan, serta kesempatan dalam pembentukan makna hidup mereka. Hasil penelitian ini mengindikasikan bahwa media digital, media sosial, serta ruang digital memiliki peran signifikan dalam proses pembentukan identitas diri dan pencarian makna hidup generasi Z, namun di sisi lain turut memunculkan tantangan berupa gangguan digital, krisis identitas, serta kekhawatiran terhadap masa depan. Faktor keluarga, komunitas sosial, pendidikan, dan kemampuan dalam penggunaan teknologi informasi bisa memainkan peran dalam membantu anak-anak Gen Z mencari arti hidup yang asli, spiritual, dan membawa dampak positif di zaman digital. Penelitian ini menekankan bahwa kerjasama antara keluarga, sekolah, dan komunitas sangat penting untuk meningkatkan kemampuan literasi digital dan kesadaran diri, sehingga generasi Z dapat memanfaatkan teknologi dengan bijak dalam mencari arah dan makna hidup mereka.